Shoaling with Fish : Using Miniature Robotic Agents to Close the Interaction Loop with Groups of Zebrafish Danio rerio /: Using Miniature Robotic Agents to Close the Interaction Loop with Groups of Zebrafish Danio rerio. ([2019]) - Bonnet, Frank; Mondada, Francesco
No abstract available